Gestão de processo: uma proposta de padronização de um arranjo físico em uma indústria de estofados localizada no sudoeste do Paraná - Lazarotto, Luana (2020)
The Layout Production Influences several aspects of the production process, which may affect production costs and the safety of employees. Defining or organizing physical requires the use of tools to obtain the best result. No present work to conclude a post-graduate course in Production Engineering aimed at analyzing a furniture industry located in Francisco Beltrão - Paraná, where it is produced with custom upholstery, with this, it was observed the various types of existing arrangements and analysis of the space and production flow of the studied company. Thus, a proposal for improving the flow was proposed from the interrelation diagram, where the current physical arrangement contemplates the process flow and does not have a standardization of the arrangement.